PA-X protein of H1N1 subtype influenza virus disables the nasal mucosal dendritic cells for strengthening virulence - Tao Qin; Yulian Chen; Dandan Huangfu; Yinyan Yin; Xinyu Miao; Yuncong Yin; Sujuan Chen; Daxin Peng; Xiufan Liu (Virulence, 2022)
PA-X protein arises from a ribosomal frameshift in the PA of influenza A virus (IAV). However, the immune regulatory effect of the PA-X protein of H1N1 viruses on the nasal mucosal system remains unclear. Here, a PA-X deficient H1N1 rPR8 viral strain (rPR8-△PAX) was generated and its pathogenicity was determined. The results showed that PA-X was a pro-virulence factor in mice. Furthermore, it reduced the ability of H1N1 viruses to infect dendritic cells (DCs), the regulator of the mucosal immune system, but not non-immune cells (DF-1 and Calu-3). Following intranasal infection of mice, CCL20, a chemokine that monitors the recruitment of submucosal DCs, was downregulated by PA-X, resulting in an inhibition of the recruitment of CD11b+ DCs to submucosa. It also attenuated the migration of CCR7+ DCs to cervical lymph nodes and inhibited DC maturation with low MHC II and CD40 expression. Moreover, PA-X suppressed the maturation of phenotypic markers (CD80, CD86, CD40, and MHC II) and the levels of secreted pro-inflammatory cytokines (IL-1β, IL-6, and TNF-α) while enhancing endocytosis and levels of anti-inflammatory IL-10 in vitro, suggesting an impaired maturation of DCs that the key step for the activation of downstream immune responses. These findings suggested that the PA-X protein played a critical role in escaping the immune response of nasal mucosal DCs for increasing the virulence of H1N1 viruses.